Prescription Opioids for Occupational Injury: Results from Workers' Compensation Claims Records. Issue 9 (18th March 2014) - Berecki‐Gisolf, Janneke; Collie, Alex; McClure, Roderick J.
Abstract Objective The objective of this study is to identify the prevalence of opioid prescription use in an Australian workers' compensation population and assess predictors of long‐term use. Design Retrospective administrative data analysis. Setting WorkSafe Victoria (Australia) workers' compensation. Subjects Workers with a workers' compensation claim were included if the injury/illness started in 2008 or 2009 (N = 54, 931). Methods Claim payments records dating up to 2 years postinjury were analyzed to determine receipt of prescription opioids. Long‐term use was defined as use of any opioid beyond 1 year postinjury. Results Within the follow‐up period, 8, 933 (16.3%) workers claimed prescription opioids: 10.0% claimed opioids in the first year only, and 6.3% claimed opioids beyond the first year. The most commonly received opioids were codeine (10.4%), oxycodone (7.5%), and tramadol (5.0%). Dextropropoxyphene, which is considered unsafe in many countries because of potentially fatal side effects, was used by 1.9% of injured workers. Progression to long‐term use of opioids was common (N = 3, 446; 39%): age (35–64 years; the association with age followed an inverse U‐shaped curve), women, laborers, lower socioeconomic status, greater work disability, and greater hospital expense were associated with opioid use beyond the first year postinjury. Conclusion Prescription opioid use for workplace injury in Australia is common but not as common as reports from U.S. workers' compensation schemes. The type of opioid and number of repeat prescriptions are factors that should be carefully considered by practitioners prescribing opioids to injured workers: progression to long‐term use is common and not fully explained by injury severity.